2016
DOI: 10.1177/1933719115602773
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nutrient Restriction in Guinea Pigs as an Animal Model for Inducing Fetal Growth Restriction

Abstract: We determined the impact of moderate maternal nutrient restriction (MNR) in guinea pigs on pregnancy outcomes, maternal/fetal growth parameters, and blood analytes to further characterize the utility of this model for inducing fetal growth restriction (FGR). Thirty guinea pig sows were fed ad libitum (Control) or 70% of the control diet prepregnant switching to 90% at midpregnancy (MNR). Animals were necropsied near term with weights obtained on all sows, fetuses, and placenta. Fetal blood sampling and organ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 51 publications
7
58
0
Order By: Relevance
“…As this is apparently not the case in guinea pigs, it can be concluded that these animals are able to accumulate additional energy reserves during gestation, which may be enhanced by feeding on dietary PUFAs. A lower litter size and total litter mass in SFA females may have further been related to less pronounced placental tissues [48], which perhaps also caused a decreased energy allocation in establishing and maintaining these tissues. This would also be supported by a general positive link to the total litter mass, as more and heavier fetuses require more space in the uterus and have to be provided with more oxygen and nutrients, resulting in larger and heavier placentas [41].…”
Section: Discussionmentioning
confidence: 99%
“…As this is apparently not the case in guinea pigs, it can be concluded that these animals are able to accumulate additional energy reserves during gestation, which may be enhanced by feeding on dietary PUFAs. A lower litter size and total litter mass in SFA females may have further been related to less pronounced placental tissues [48], which perhaps also caused a decreased energy allocation in establishing and maintaining these tissues. This would also be supported by a general positive link to the total litter mass, as more and heavier fetuses require more space in the uterus and have to be provided with more oxygen and nutrients, resulting in larger and heavier placentas [41].…”
Section: Discussionmentioning
confidence: 99%
“…Sows delivered spontaneously at term (∼67 days) and birth weight was recorded. Guinea pig pups from a UAA pregnancy weighing less than 85 grams were defined as LBW, and pups weighing 90 grams or greater at birth were defined as NBW (Elias et al, 2015). Five days prior to weaning the postnatal control diet (CD, TD: 110240; Harlan Laboratories, Madison, WI, USA) was introduced to the pups through the maternal feeding tray.…”
Section: Methodsmentioning
confidence: 99%
“…Human and animal studies of food restriction during pregnancy confirm that maternal undernourishment leads to IUGR depending upon the timing (pre-vs postconception) and severity of the insult [28,29,[55][56][57]. Moreover, like models of uterine ligation, fetal liver growth from MNR dams is compromised at birth followed by rapid postnatal catch-up growth [36,55,58].…”
Section: Maternal Nutrient Restriction (Mnr) Model Of Undernutritionmentioning
confidence: 99%
“…Moreover, like models of uterine ligation, fetal liver growth from MNR dams is compromised at birth followed by rapid postnatal catch-up growth [36,55,58]. However, with models of MNR, the impact of a decrease in maternal and placental weight during pregnancy must also be taken into consideration [55,59]. Sheep and rat studies have demonstrated that MNR leads to glucose intolerance and insulin insensitivity, along with greater hepatic lipid and glycogen content in the offspring [58,60].…”
Section: Maternal Nutrient Restriction (Mnr) Model Of Undernutritionmentioning
confidence: 99%
See 1 more Smart Citation